Modelación de la propagación de armónicos en sistemas de transmisión eléctrica - Ayala Criollo, Cristian Mauricio (2017)
This paper presents the modeling of the harmonics propagation in the electrical transmission lines, to define the effect of voltage and current signals; and consequently, determine your energy quality. For the purposes of the study, the analysis of the signals from the nonlinear sources is carried out and it is introduced in the electrical power systems by the use of non-parametric methods, which involves time domain analysis and Time domain - Frequency. For the model of the transmission lines is done by the π model of the parameters distributed in long lines. For modeling and simulation, the overlap of harmonics and the coincidence factor of nonlinear signals in a common node were considered. Finally, the harmonic percentages that affect the long lines are shown in relation to the number of signals no line injected to the node to determine the voltage and current waveform.